Protesting is Necessary: Social Movement MST and the “500 years” of Brazil in the Portuguese Media - Barbalho, Alexandre (2015)
This paper analyzes the presence of the social movement called Movimiento de Trabajadores Rurales Sin Tierra (MST) in the Portuguese press coverage for the celebration of the 500th anniversary of Brazil. In this essay, its author seeks to understand how this social movement can —if it can— give some guidelines to the press. The survey was conducted in four daily newspapers (Public, Correio da Manha, Diário de Notícias and Jornal de Notícias), a weekly newspaper (Expresso), and a weekly magazine (Visão). The journalistic articles that were not limited to the description of events were explored, thus allowing access to speeches and subject positions of MST. For the analysis of materials, theoretical and methodological support of the Theory of Speech was used.